Study of the Nuclear Structure of some Neutron Rich Si Isotopes Using Shell Model with Skyrme Interaction - abbas, luma jamal; Alzubadi, Ali A. (Iraqi Journal of Physics, 2021)
Abstract      The nuclear structure of 28-40Si isotopes toward neutron dripline has been investigated in framework of shell model with Skyrme-Hrtree-Fock method using certain Skyrme parameterizations. Moreover, investigations of static properties such as nuclear densities for proton, neutron, mass, and, charge densities with their corresponding rms radii, neutron skin thicknesses, binding energies, separation energies, shell gap, and pairing gap have been performed using the most recent Skyrme parameterization. The calculated results have been compared with available experimental data to identify which of these parameterizations introduced equivalent results with the experimental data. For all dynamic properties, sdpf shell model space has been used to generate one body transition density matrix element with SDPFK two body effective interaction. The calculations also reproduced the low and higher-laying 2+ energy level scheme, and reduced transition probability B(E2) for even Si-isotopes.